Nuclei of Meaning That Emerge from the Experience of Human Rights Training in In-Service Teachers and Pedagogy Students from a Chilean State University [Núcleos de Sentido Que Emergen Desde la Experiencia de Formación en Derechos Humanos en Docentes en Ejercicio y Estudiantes de Pedagogía de Una Universidad Estatal de Chile] - Contreras-Salinas, S (Universidad Austral de Chile, 2017)
The article presents findings of a study whose objective was to unveil the meanings that the experience of training in Human Rights during the process of initial teacher training acquires for pedagogical practice. Six teachers who work in different disciplines, in addition to eleven students from pedagogy careers distributed in two groups, participated in the study. We used informal interviews, discussion groups, and collective narrative methods. The analysis was performed through the detection of nuclei of meaning, within the framework of the application of the Systematization of Experiences. The meanings that emerged triggered subjective and intersubjective processes, which allowed participants to be resituated as subjects. It is concluded that it is necessary to strengthen teacher training and pedagogical action with a human rights approach and to mobilize a humanizing process aimed at re-establishing social ties in and from the multiplicity of vulnerabilities. © 2017 Universidad Austral de Chile.